(untitled) (Impact: Journal of Transformation, 2019)
Occupational stress is stress caused by work-related factors which are detrimental to employees’ wellbeing and effectiveness in the workplace. In previous studies conducted, 96% of teaching and non- teaching staff indicated that stress has negative effects on job performance and this is associated with psychological and physiological illnesses which occasionally affect their effectiveness in the workplace (Chukwuma, 2017). Identifying the sources of occupational stress will enable both leaders and individual employees in higher educational institutions to manage stress appropriately. The wellbeing of employees plays a significant role in achieving organizational goals. In higher education, leaders require employees to work sufficiently towards the success of the institution in promoting quality education within its threshold. This study is based on quantitative research methods conducted in West Africa Theological Seminary Lagos, Nigeria, to determine the sources of occupational stress and its effect on workers’ effectiveness in the workplace. The descriptive survey design was adopted to describe the phenomenon under study. Purposive sampling technique was used to gather information from the respondents. Pertinent data were collected through a questionnaire based on open and closed-ended questions. Subsequently, the regression model was used to test the significant relationship between variables. The key areas covered in the literature focused on the sources of occupational stress, the effect of job stress and stress management.